The webquest as a didactic resource for the promotion of significant learning in natural and exact sciences - Cordova, Rafael Silva (2020)
The Webquest is a type of didactic activity based on constructivist assumptions of the teaching - learning process. This research, in the context of innovation, proposes a didactic experience for three groups of teachers, to design, develop and implement webquest for the teaching of science. It is guided by a guided indagatory methodology that promotes meaningful learning and improves academic performance. The methodological teaching proposal is theoretically based on the significant learning of Ausubel, on cognitive developments of Piaget, zone of proximal development of Vygotsky and the cooperative work of Jonhson and Jonhson. The research is experimental, essentially quantitative, with an exploratory, descriptive study. The results ensure an important advance between the pretest and posttest of each work group, with a tangible product that can be used in the science classrooms.